Artocarmitin B enhances intracellular antioxidant capacity via activation of Nrf2 signaling pathway in human lung epithelial cells. (1st September 2019) - Wu, Xue-Yi; Chen, Xue-Mei; Zhou, Ming-Xing; Hu, Hui-Xin; Zhang, Jiao-Zhen; Wang, Xiao-Ning; Ren, Dong-Mei; Lou, Hong-Xiang; Shen, Tao
Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) plays a key role in redox homeostasis. Activation of Nrf2 pathway by natural molecules effectively inhibits oxidants and toxicants-induced redox imbalance, and thus is able to intervene the onset and progression of many human diseases. In our previous study, a chalcone named as artocarmitin B (ACB), formed by artocarmitin A (ACA) and a trans -feruloyl substituent, was found to be a potential Nrf2 activator. In the present research, we found that ACB up-regulated the expressions of Nrf2, NAD(P)H: quinone oxidoreductase 1 (NQO1) and glutamate-cysteine ligase, modifier subunit (GCLM), inhibited Nrf2 degradation and promoted Nrf2 translocation to the nucleus under non-toxic doses. Moreover, ACB enhanced intracellular antioxidant capability in human lung epithelial cells through up-regulating reduced glutathione (GSH) level. Furthermore, ACB-induced activation of Nrf2 was related to the kinase pathways, including mitogen-activated protein kinase (MAPK), protein kinase C (PKC), phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K), and protein kinase R-like endoplasmic reticulum kinase (PERK). In terms of activation of Nrf2 pathway, ACB was more potent than ACA and ferulic acid (FA) individually or in combination. Collectively, our results indicate that ACB is an novel Nrf2 activator and enhances intracellular antioxidant capacity in human lung epithelial cells. Graphical abstract: Image 1 Highlights: ACB is firstly identified to be an activator of Nrf2 pathway. ACB enhances antioxidant capability in human lung epithelial cells. ACB-induced Nrf2 activation requires PI3K, MAPKs, PKC and PERK kinases. The Nrf2 activation by ACB is stronger than that of combined effect of ACA and FA.